Dynamic and Hybrid Configurations for Extracorporeal Membrane Oxygenation: An Analysis of the Chinese Extracorporeal Life Support Registry. Issue 4 (3rd August 2021) - Li, Chenglong; Xie, Haixiu; Li, Jun; Qin, Bingyu; Lu, Junyu; Zhang, Jinsong; Lv, Liwen; Li, Binfei; Zhou, Chengbin; Yin, Yongjie; Qiu, Haibo; Li, Yimin; et al.
Abstract : Dynamic or hybrid configurations for extracorporeal membrane oxygenation (ECMO) are needed when patient physiology or clinical conditions change. Dynamic configurations included configurations converting from veno-arterial (V-A) ECMO or veno-venous (V-V) ECMO to other forms. Hybrid configurations included venous-arteriovenous (V-AV) and venovenous-arterial (VV-A) ECMO. This study retrospectively analyzed a total of 3, 814 ECMO cases (3, 102 adult cases) reported to the Chinese Society of Extracorporeal Life Support from January 1, 2017 to December 31, 2019. Eight-three adult patients had dynamic or hybrid ECMO configurations, whose primary diagnoses included cardiogenic shock (33.7%), cardiac arrest (6.0%), acute respiratory failure (39.8%), septic shock (9.6%), multiple trauma (3.6%), pulmonary hypertension (3.6%), and others (3.6%). Configuration changes occurred in 37 patients with the initial configuration of VA (20 to VV, 13 to V-AV, and 4 to VV-A) and 27 with the initial configuration of VV (7 to VA, and 20 to V-AV). A total of 46 (55.4%) patients received hybrid configurations of V-AV and 10 (12.0%) received VV-A. Patients with the initial configuration of VV who converted to other configurations had higher in-hospital mortality (74.1%) than other initial configurations (VA 45.9%, V-AV 76.9%, VV-A 66.7%, P = 0.021). We concluded that dynamic or hybrid ECMO configurations were used in various underlying diseases, in which V-AV was most commonly used. Patients receiving VV ECMO for respiratory support initially, who then converted to other configurations for both respiratory and circulatory support, had significantly worst outcomes among the groups studied. The initial configuration should be selected carefully after thorough assessment of patient condition.